2019
DOI: 10.3390/en12173245
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Effects of Weak Interfaces on Fracture Height Containment in Hydraulic Fracturing

Abstract: Hydraulic fracturing is an effective method for developing unconventional reservoirs. The fracture height is a critical geometric parameter for fracturing design but will be limited by a weak interface. Fracture containment occurs when fracture propagation terminates at layer interfaces that are weaker than the surrounding rock. It always occurs in multilayer formation. Therefore, the mechanism of fracture height containment guides fracture height control in hydraulic fracturing. In order to study the fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
(51 reference statements)
0
12
0
Order By: Relevance
“…One surface is regarded as the target surface, and the other is considered the contact surface. The details of BDEM were introduced and elaborated on in our previous work (Zheng et al, 2019a andZheng et al, 2019b).…”
Section: Numerical Model and Validationmentioning
confidence: 99%
See 3 more Smart Citations
“…One surface is regarded as the target surface, and the other is considered the contact surface. The details of BDEM were introduced and elaborated on in our previous work (Zheng et al, 2019a andZheng et al, 2019b).…”
Section: Numerical Model and Validationmentioning
confidence: 99%
“…Furthermore, the approach angle between the fracture and the bedding plane also affects the propagation behavior. The study of Zheng et al (2019b) indicated that a longer main fracture may form at a higher approach angle if the cementation of BPs is not weak. On the contrary, for fracture propagation in BPs, stress intervention, smaller injection rate, and smaller fluid viscosity are useful in general.…”
Section: Figure 13mentioning
confidence: 99%
See 2 more Smart Citations
“…They discovered that even when the interface strength is low, hydraulic fractures can penetrate the lithologic interface if the vertical stress difference and interface angle are large enough. When the included angle between the hydraulic fracture and the interface is less than 45 • and the tensile strength ratio of the pay layer and the interlayer is less than 0.3, the hydraulic fracture cannot penetrate the interface no matter how large the vertical stress difference is [13,14]. Some studies experimentally discovered that the fracture can directly penetrate the interface only when the vertical stress reaches a certain threshold, but the threshold gradually increases with the decrease in the interface friction coefficient [15,16].…”
Section: Introductionmentioning
confidence: 99%